Connective tissue disease related interstitial lung disease: a single center experience - Gezgin, Tahsin; Atilla, Nurhan; Yıldırım Çetin, Gözde; Akkök, Burcu; Bozkuş, Fulsen; Kızıldağ, Betül; Çulpan, Ali; Kahraman, Hasan (The European Research Journal, 2023)
Objectives: We aimed to determine the clinical features of the patients followed by our hospital with the diagnosis of connective tissue disease related interstitial lung disease (CTD-ILD). Methods: The study included 113 patients who were followed up with the diagnosis of CTD-ILD, admitted to Kahramanmaraş Sütçü İmam University, Faculty of Medicine, Rheumatology Department between January 2019 and December 2020. Demographic characteristics, laboratory data and high-resolution computed tomography (HRCT) patterns of the patients were recorded retrospectively. Results: Of 113 patients diagnosed with CTD-ILD; 90 were female, 23 were male. When the distribution of connective tissue disease (CTD) evaluated; 50 were rheumatoid arthritis, 41 were systemic sclerosis, 8 were sjogren’s syndrome, 4 were systemic lupus erythematosus, 7 were overlap syndrome and 3 were undifferentiated connective tissue disease. There was no statistically significant difference between laboratory parameters. In the HRCT evaluation, 86 patients had nonspecific interstitial pneumonia (NSIP), 25 patients had usual interstitial pneumonia (UIP), and 2 patients had lymphocytic interstitial pneumonia (LIP) pattern. The most common pattern, including rheumatoid arthritis, was NSIP. Conclusions: In our study, as inconsistent with the literature the most common pattern in RA patients was found to be NSIP.